Psoriasis and cancer. An Australian/New Zealand narrative. (10th July 2018) - Rademaker, Marius; Rubel, Diana M; Agnew, Karen; Andrews, Megan; Armour, Katherine Sarah; Baker, Christopher; Foley, Peter; Gebauer, Kurt; Goh, Michelle SY; Gupta, Monisha; Marshman, Gillian; Prince, H Miles; et al.
Abstract: Patients with psoriasis have an increased risk of cancer, which may be due to impaired immune surveillance, immune modulatory treatments, chronic inflammation and/or co‐risk factors such as obesity. The increase in treatment‐independent solid cancers, including urinary/bladder cancers, oropharynx/larynx, liver/gallbladder and colon/rectal cancers, seem to be linked to alcohol and smoking. Lung cancer and nonmelanoma skin cancer are also increased in patients with psoriasis. The risk of nonmelanoma skin cancer increases with age and severity of psoriasis. It is also higher in men, particularly for squamous cell carcinoma, which may reflect previous exposure to PUVA and/or ciclosporin. The risk of cutaneous T‐cell lymphoma is substantially higher in patients with moderate‐to‐severe psoriasis. Biologic therapies are independently associated with a slight increase risk of cancer, but this is less than ciclosporin, with the risk confounded by disease severity and other co‐risk factors. The risk of cancer from low‐dose methotrexate is likely minimal. In contrast, acitretin is likely protective against a variety of solid and haematological malignancies. The data on small molecule therapies such as apremilast are too immature for comment, although no signal has yet been identified. The decision whether to stop psoriasis immune modulatory treatments following a diagnosis of cancer, and when to resume, needs to be considered in the context of the patients' specific cancer. However, there is no absolute need to stop any treatment other than possibly ciclosporin, unless there is a concern over an increased risk of serious infection or drug–drug interaction with cancer‐directed therapies, including radiotherapy.